Экспериментальное исследование компонент тензорной анализирующей способности реакции γD → PPπ-; Известия вузов. Физика; Т. 59, № 6 - Гаузштейн В. В. Вячеслав Валерьевич; Грамолин А. В. Александр Валерьевич; Василишин Б. И. Богдан Иванович; Зеваков С. А. Сергей Александрович; Логинов А. Ю. Алексей Юрьевич; Николенко Д. М. Дмитрий Митрофанович; Рачек И. А. Игорь Анатольевич; Садыков Р. Ш. Рустам Шагитович; Топорков Д. К. Дмитрий Константинович; Шестаков Ю. В. Юрий Владимирович; Афанасьев К. В. Константин Вадимович; Левчук М. И. Михаил Иванович; et al. (2016, 2016)
Заглавие с экрана